Analysis of Sugar Biosynthesis-Related Proteins of Sorghum Bicolor and Investigation of their Role in Drought-Stress Tolerance - Prof. Prafulla Kumar Das, Mr. Subham Acharya, Ms. Babita Sharma (International Journal of Modern Agriculture, 2020)
The world's major production constraint consists of drought alone or in combination with the other stresses. Drought alone or in conjunction with stresses, sorghum, one of the major cereal crops, has been affected; however, sorghum has evolved adaptive responses to combined stresses. Drying stress causes remarkable changes in physiology and growth impediments that decrease the plant biomass and crop yields significantly. Some plant species, however, are resilient and keep their yields almost normal under severe water deficits. Sorghum's two-dimensional difference gel electrophoresis (2D-DIGE) was tested for its adaptive response against drought stress and landraces from Egypt. Their relative control values following the stress of drought and recovery were compared to the physiological measurements and proteomic alterations in accession number 11434, drought resistant and accession number 11431, drought sensitive. In addition, a significant number of genes of sorghum for drought tolerance were investigated. However, there is a little understanding of the molecular mechanism underlying the drought response. The variation in amino acids, polysaccharides and their derivatives is a part of the metabolic changes. A total of 188 compounds were found in the two sorghum varieties, including 142 recognized metabolites and 46 unknown small molecules. This study provides the candidates genes of Sorghum bicolor responsible for the drought-stress tolerance..